(3CeGdj GdTLQjs - (3jMji Hf GdMSjf Hf ESeGYjd GdTLQj, CHh GdMSf, GdeQTO HGddg , J (B479 (3g` s ((3eMeO Hf GSYO Hf Ydi GdLQGYi GdHZhi GdaGQSi s)
(3ChdgG (B:s
(3bGd eMeO Hf CMeO Hf Ydi Hf CMeO Hf GdhdjO Jhdi Gddg Jhajbg heYhfJg GdMeO ddg GdChd GdCNQ GdHGWf GdXGgQ GeG HYO aEf deG hQO Yf GdfHi GdJQZjH ai LejY cdGeI hGdMK Ydi MaX s
(3BNQgG (B:s
(3jWGdH GSe Gddg GdGYXe ade jQTjfG abGd dGjJegG GQHYjf jhekG bO Nd GdeSLO aEPG QbYI ajgG ecJhH jGfhQ GdfhQ Je GdeLdO GdChd ef cJGH GdGQHYjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs